The impact of depression on mortality among older adult patients with hypertension: a systematic review and meta-analysis - Fang, Ze; Huang, Tao; Zhang, Qiongfang; Shi, Lili; Huang, Rui (Frontiers in Public Health, 2025)
BackgroundDepression and hypertension frequently coexist in the older adult and may jointly contribute to increased mortality and cardiovascular risk. However, the extent to which depression independently affects these outcomes remains unclear. This systematic review and meta-analysis aimed to evaluate the association between depression and all-cause mortality in older adult patients with hypertension.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and Web of Science (2010–2024) for relevant cohort studies and randomized controlled trials. Pooled hazard ratios (HRs) were calculated using a random-effects model. Subgroup and sensitivity analyses were performed. The study protocol was registered in PROSPERO (CRD420251019904).ResultsThirteen studies including 483,560 participants showed that depression was associated with increased all-cause mortality (HR = 1.32, 95% CI: 1.23–1.41). The association was stronger among females (HR = 1.57) and in studies with short-term follow-up (<10 years, HR = 1.40). The findings were consistent across different depression assessment tools.ConclusionDepression is independently associated with higher all-cause mortality in older adult hypertensive patients. Routine screening and management of depression—particularly among older women—may improve long-term outcomes. Further interventional studies are needed to evaluate the prognostic impact of depression treatment in this population.Systematic review registrationThe systematic review was registered with PROSPERO (CRD420251019904).